2004
DOI: 10.1021/np040099d
|View full text |Cite
|
Sign up to set email alerts
|

Cadinane Sesquiterpenes from the Brown Alga Dictyopteris divaricata

Abstract: Seven new cadinane sesquiterpenes, (-)-(1R,6S,7S,10R)-1-hydroxycadinan-3-en-5-one (1), (+)-(1R,5S,6R,7S, 10R)-cadinan-3-ene-1,5-diol (2), (+)-(1R,5R,6R,7S,10R)-cadinan-3-ene-1,5-diol (3), (+)-(1R,5S,6R,7S,10R)-cadinan-4(11)-ene-1,5-diol (4), (+)-(1R,5R,6R,7R,10R)-cadinan-4(11)-ene-1,5,12-triol (5), (-)-(1R,4R,5S,6R,7S, 10R)-cadinan-1,4,5-triol (6), and (-)-(1R,6R,7S,10R)-11-oxocadinan-4-en-1-ol (7), together with nine known compounds were isolated from the brown alga Dictyopteris divaricata. The structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
(35 reference statements)
1
33
1
Order By: Relevance
“…The 13 C-NMR spectrum along with the DEPT and HSQC experiments revealed the presence of four methyls, four methylenes, five methines, and two quaternary carbon atoms. A detailed comparison of the above spectral data with those reported for cadinan-1,4,5-triol ( 2 ) revealed that 1 differed from 2 mainly at C-4 and C-5 [5], so 1 could be a dehydrated product of 2 between the hydroxyl groups at C-4 and C-5 according to the upfield-shifted C-4, C-5, and H-5 [10]. The 1 H- 1 H COSY correlations as shown in Table 1 and the observed HMBC (Figure 2) correlations from H-12 to C-7, C-11, and C-13, from H-13 to C-7, C-11, and C-12, from H-14 to C-1, C-9, and C-10, from H-15 to C-3, C-4, and C-5, from H-5 to C-1, C-4, C-6, and C-15, and from HO-1 to C-1, C-6, and C-10 confirmed the gross structure of 1 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 13 C-NMR spectrum along with the DEPT and HSQC experiments revealed the presence of four methyls, four methylenes, five methines, and two quaternary carbon atoms. A detailed comparison of the above spectral data with those reported for cadinan-1,4,5-triol ( 2 ) revealed that 1 differed from 2 mainly at C-4 and C-5 [5], so 1 could be a dehydrated product of 2 between the hydroxyl groups at C-4 and C-5 according to the upfield-shifted C-4, C-5, and H-5 [10]. The 1 H- 1 H COSY correlations as shown in Table 1 and the observed HMBC (Figure 2) correlations from H-12 to C-7, C-11, and C-13, from H-13 to C-7, C-11, and C-12, from H-14 to C-1, C-9, and C-10, from H-15 to C-3, C-4, and C-5, from H-5 to C-1, C-4, C-6, and C-15, and from HO-1 to C-1, C-6, and C-10 confirmed the gross structure of 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Continuing chemical investigation of the secondary metabolites of D. divaricata collected off the coast of Yantai has led to the isolation of one new cadinane sesquiterpene, 4 β ,5 β -epoxycadinan-1 β -ol ( 1 ), and six known cadinane sesquiterpenes: cadinan-1,4,5-triol ( 2 ) [5], 4 α ,5 β -dihydroxycubenol ( 3 ) [6], cubenol ( 4 ) [6], cadinan-3-ene-1,5-diol ( 5 ) [5], cubenol-3-one ( 6 ) [6], and torreyol ( 7 ) [6]. The isolation of compounds 1 – 7 and structural determination of compound 1 are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated sesquiterpenes (whose main sources are the red algae) are reported in Padina antillarum (Parameswaran et al, 1994(Parameswaran et al, , 1996 and Dictyopteris divaricata , and sesquiterpenes without halogens in Dictyopteris divaricata (Song et al, 2005(Song et al, , 2006Qiao et al, 2009;Wen et al, 2009), D. undulata (Song et al, 2004a) and Taonia atomaria (De Rosa et al, 1994). For the latter two genera, 36 and six species are recognized, respectively, while for Padina 37 species are still valid.…”
Section: Resultsmentioning
confidence: 99%
“…The marine brown alga Dictyopteris divaricata , found widely spread along the coasts of China, has provided many structurally interesting sesquiterpenes and norsesquiterpenes [14]. However, to date there have been no reports of halogenated structures isolated from this species.…”
Section: Introductionmentioning
confidence: 99%